Penerapan Hukum Administrasi Negara dalam Membangun Pemerintahan yang Baik - Latifa, Asma; Frinaldi, Aldri; Roberia, Roberia (Medan Resource Center, 2024)
This study examines the application of administrative law in establishing good governance. The background of this research is rooted in the increasing demand for transparent, accountable, and effective governance to address public administration challenges. The research question focuses on how administrative law can be effectively implemented to foster good governance practices. Using a qualitative approach, this study employs document analysis and in-depth interviews with legal experts and government officials to gather comprehensive insights. The results indicate that robust administrative legal frameworks significantly enhance governance by promoting transparency, accountability, and public participation. Furthermore, the findings highlight the importance of continuous legal reforms and capacity-building initiatives to address existing gaps and challenges. The conclusion of this study asserts that the effective application of administrative law is crucial in achieving good governance, as it provides a structured mechanism for oversight and accountability. This research contributes to the ongoing discourse on governance reforms by offering practical recommendations for policymakers and administrators to strengthen legal frameworks and governance practices.